Efek Parameter Feeding dan Kondisi Geometri Cutter terhadap Kekasaran Permukaan Baja ST 60 pada Proses Milling Vertikal - Marianus Beatriks Djala Gili; Darto Darto; Agus Iswantoko; Surjedi Surjedi (TRANSMISI, 2022)
The milling process is one type of conventional machining process that is often carried out. The surface quality of the workpiece produced in the milling process is influenced by several factors, including the speed of feeding and the condition of the cutter. The aim of this study was to determine the effect of variable feeding and cutter conditions on the surface roughness of steel in conventional milling processes. The research was conducted using an experimental method. The research object is ST 60 steel which is processed on a micron milling machine WF3 SA. The research data shows that the feeding speed affects the surface roughness quality, where the greater the feeding value, the greater the Ra value. In addition, the condition of the cutter also has an effect, where slashing using a new cutter produces a Ra value which tends to be lower than slashing using a sharpened cutter. The lowest Ra value is 0.45 m occurs at 10 mm/minute feeding using a new cutter. While the highest Ra value at 40mm/minute feeding is 1.54 m using a sharpening cutter.